The value of intuition in selecting debridement aids for the removal of hyperkeratosis: an introspective study - Fania Pagnamenta; Sophie Robson; Linda Mason (British Journal of Community Nursing, 2026)
Background Effective leg ulcer care includes the removal of hyperkeratosis, a thick, adherent layer of dead skin. In the UK, available methods to remove hyperkeratosis include debridement pads, pre-impregnated cloths and tenotomes. However, evidence supporting their efficacy remains limited. Aims This study aimed to explore how expert clinical intuition can inform a protocol to guide less-experienced nurses in selecting appropriate methods for hyperkeratosis debridement. Methods Drawing on Benner's ‘novice to expert’ model, three highly experienced nurses observed each other's practice while debriding hyperkeratosis in leg ulcer patients. Standard of care was maintained throughout. Findings Tenotomes were consistently the most effective, removing adherent scales efficiently. Debridement pads removed only loose debris, while pre-impregnated cloths were ineffective for stubborn scales but useful for rehydration post-tenotome use. Conclusions: A simple protocol recommending tenotomes for hyperkeratosis removal was developed. Further research is needed to evaluate its implementation in clinical practice. Implications for practice: The protocol offers practical guidance for selecting hyperkeratosis debridement methods and may support more consistent leg ulcer care.